Inactivation of the spxA1 or spxA2 gene of Streptococcus mutans decreases virulence in the rat caries model. (16th May 2016) - Galvão, L.C.C.; Rosalen, P.L.; Rivera‐Ramos, I.; Franco, G.C.N.; Kajfasz, J.K.; Abranches, J.; Bueno‐Silva, B.; Koo, H.; Lemos, J.A.
Summary: In oral biofilms, the major environmental challenges encountered by Streptococcus mutans are acid and oxidative stresses. Previously, we showed that the transcriptional regulators SpxA1 and SpxA2 are involved in general stress survival of S. mutans with SpxA1 playing a primary role in activation of antioxidant and detoxification strategies whereas SpxA2 serves as a back up activator of oxidative stress genes. We have also found that spxA1 mutant strains (∆ spxA1 and ∆ spxA1 ∆ spxA2 ) are outcompeted by peroxigenic oral streptococci in vitro and have impaired abilities to colonize the teeth of rats fed a highly cariogenic diet. Here, we show that the Spx proteins can also exert regulatory roles in the expression of additional virulence attributes of S. mutans . Competence activation is significantly impaired in Δ spx strains and the production of mutacin IV and V is virtually abolished in Δ spxA1 strains. Unexpectedly, the ∆ spxA2 strain showed increased production of glucans from sucrose, without affecting the total amount of bacteria within biofilms when compared with the parent strain. By using the rat caries model, we showed that the capacity of the Δ spxA1 and Δ spxA2 strains to cause caries on smooth tooth surfaces is significantly impaired. The ∆ spxA2 strain also formed fewer lesions on sulcal surfaces. This report reveals that global regulation via Spx contributes to the cariogenic potential of S. mutans and highlights that animal models are essential in the characterization of bacterial traits implicated in virulence.